Ray Tracing of Various Surface Light Trapping Structures on Silicon Solar Cells - Omar, Halo D. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2026)
In this work, the SunSolve ray tracer is used to investigate the effects of various surface structures on silicon (Si) passivated emitter and rear cell (PERC) solar cells. A Si substrate with a thickness of 170 µm is used. The studied surface structures include front-side inverted pyramids, cones, and spherical caps. Flat Si is used as a reference. The performance of these structures is evaluated across the 200–1100 nm wavelength range under AM 1.5G solar spectrum illumination at normal incidence. The weighted average reflectance (RWAR) is calculated from the reflectance profile over the entire spectral range. Among the results, the PERC solar cell with a pyramid texture demonstrates a short-circuit current density (Jsc) of up to 40.55 mA/cm2 and a conversion efficiency (η) of 21.76%. This represents a significant performance improvement over the other structures, attributed to enhanced broadband light absorbance and increased device efficiency. This study thus provides a detailed analysis of how different front-surface structures affect the performance of Si photovoltaic cells.